Overview of Sensorineural Deafness Patients at Cut Meutia General Hospital, North Aceh, Indonesia - Hafni, Ahmad; Yanti, Lisa (Sriwijaya Journal of Otorhinolaryngology, 2023)
Introduction: Sensorineural deafness is deafness that occurs due to disturbances in the inner ear or in the nerve pathways from the inner ear to the brain. This study aimed to provide an overview of sensorineural deaf patients at Cut Meutia General Hospital, North Aceh, Indonesia. Methods: This study was a descriptive observational study and used secondary data obtained from medical record data at the medical records installation of Cut Meutia General Hospital. A total of 50 research subjects participated in this study, and the research subjects met the inclusion criteria. The inclusion criteria in this study were patients aged > 18 years who were diagnosed with sensorineural hearing loss at Cut Meutia General Hospital, North Aceh, Indonesia, for the January-December 2022 period and had complete medical record data. Results: The majority of research subjects have an age range of > 50 years. Subject the majority of studies have male gender. The majority of research subjects complained of deafness in both ears. The majority of research subjects have a profound hearing threshold. Conclusion: Characteristics of sensorineural deafness at Cut Meutia General Hospital, North Aceh, Indonesia, generally occur at the age of > 50 years, male gender, occurs bilaterally, and has a very poor hearing threshold.